Prediction of Turbine Needed For Future Hydropower Projects in Nepal - Panta, Subash; Lamsal, Manish; Thapa, Bhola; Thapa, Biraj Singh (Hydro Nepal: Journal of Water, Energy and Environment, 2014)
As Nepal holds significant potential for a prosperous future market in hydropower and associated business developments, the Turbine Testing Lab (TTL) at Kathmandu University, Nepal has carried out a project that focuses on scientific studies to identify optimal turbine requirements for various hydropower projects. We collected and analyzed basic design data available from different sources to identify the turbine design specifications for the upcoming hydropower projects. As a result, we developed a computer program as a tool to support this work. Findings from the current studies have shown that up to 60% of the 13000 MW capacity hydropower projects under survey stage in Nepal would need Francis type of turbine with unit size below 5 MW. This finding is also supportive to establish a basis for developing turbine manufacturing and maintenance competence in Nepal from business perspectives. DOI: http://dx.doi.org/10.3126/hn.v14i0.11250 HYDRO Nepal Journal Journal of Water, Energy and Environment Volume: 14, 2014 January Page: 23-26